Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1128/jvi.02723-15
|View full text |Cite
|
Sign up to set email alerts
|

A Single Mutation at PB1 Residue 319 Dramatically Increases the Safety of PR8 Live Attenuated Influenza Vaccine in a Murine Model without Compromising Vaccine Efficacy

Abstract: The live attenuated influenza vaccine (LAIV) is preferentially recommended for use in most children yet remains unsafe for the groups most at risk. Here we have improved the safety of a mouse-adapted live attenuated influenza vaccine containing the same attenuating amino acid mutations as in human LAIV by adding an additional mutation at PB1 residue 319. This results in a vaccine with a 20-fold decrease in protective efficacy and a 10,000-fold increase in safety.T he live attenuated influenza vaccine (LAIV) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…Previous studies have shown that the ts mutations from AA/60 attenuate PR8 significantly in mice but that they fail to attenuate Cal/09 in mice and also fail to attenuate various strains of avian influenza viruses (AIVs) in birds (30,38,51). This lack of attenuation in the genetic background of Cal/09 and AIV can be overcome by the addition of other ts or att mutations (e.g., PB1 319Q [52]) or by the insertion of an attenuating PB1 HA epitope tag (53,54). However, it is clear that the AA/60 ts mutations alone do not reproducibly confer a ts or att phenotype across diverse viral genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the ts mutations from AA/60 attenuate PR8 significantly in mice but that they fail to attenuate Cal/09 in mice and also fail to attenuate various strains of avian influenza viruses (AIVs) in birds (30,38,51). This lack of attenuation in the genetic background of Cal/09 and AIV can be overcome by the addition of other ts or att mutations (e.g., PB1 319Q [52]) or by the insertion of an attenuating PB1 HA epitope tag (53,54). However, it is clear that the AA/60 ts mutations alone do not reproducibly confer a ts or att phenotype across diverse viral genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…At the indicated times (12,24,48, and 72 h p.i. ), TCS were collected, and viral titers were determined by tissue culture infectious dose assay (TCID 50 /ml) as described previously (52). Mean values and standard deviations (SD) were calculated using Prism software.…”
Section: Methodsmentioning
confidence: 99%
“…This SGR virus was found to possess an unexpectedly high degree of temperature sensitivity, which was associated with a novel mutation in PB1 (PB1 319Q). We previously showed that this PB1 mutation confers enhanced temperature sensitivity and attenuation on an LAIV constructed in the genetic background of the IAV strain, A/PR/8/34 (PR8) [55]. Here, we describe the discovery/origin of this mutation and propose a mechanism for its temperature sensitive phenotype.…”
Section: Introductionmentioning
confidence: 83%
“…LD 50 was calculated by the method of Reed and Muench [58]. The data for PR8 319Q were reproduced from our previous work [55].…”
Section: Viral Attenuationmentioning
confidence: 99%
“…Прямое включение аттенуирующих мутаций в геном актуальных эпидемических штаммов можно рассматривать как новый перспективный подход к получению живых гриппозных вакцин [4,7,16,17,20]. Основным источником аттенуирующих мутаций, согласно данным литературы, рассматривается холодоадаптированный штамм А/Энн Арбор/6/60 (Н2N2) [10].…”
Section: в в е д е н и еunclassified